2022
DOI: 10.3389/fmed.2022.895208
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cystoid Macular Edema in Retinitis Pigmentosa: A Systematic Review and Meta-Analysis

Abstract: BackgroundTo date, various treatments for cystoid macular edema (CME) in retinitis pigmentosa (RP) have been reported. We performed a systematic review and meta-analysis to evaluate the efficacy and safety of current treatments for RP-CME.MethodsPubMed, Embase and the Cochrane library were searched from inception to August 2021. ClinicalTrials.gov, WHO ICTRP and ISRCTN were also searched for relevant studies. Only studies published in English were included. The RoB 2 tool was used to evaluate the risk of bias … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 56 publications
(224 reference statements)
0
1
0
Order By: Relevance
“…Carbonic anhydrase inhibitors (CAIs) have been used to treat RP-CME for more than 30 years [14][15][16][17]. A study showed a significant reduction in central macular thickness (CMT) compared to the baseline after treatment with topical CAIs [16]. Topical steroids have also been shown to be useful in treatment of RP-CME.…”
Section: Treatment Options For Cystoid Macular Edemamentioning
confidence: 99%
“…Carbonic anhydrase inhibitors (CAIs) have been used to treat RP-CME for more than 30 years [14][15][16][17]. A study showed a significant reduction in central macular thickness (CMT) compared to the baseline after treatment with topical CAIs [16]. Topical steroids have also been shown to be useful in treatment of RP-CME.…”
Section: Treatment Options For Cystoid Macular Edemamentioning
confidence: 99%